Rhodamine-doped aerogel random laser - de Miranda, Adriana Ramos; Pecoraro, Édison [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Giehl, Júlia Maria; Reijn, Saara-Maarit; Wetter, Niklaus Ursus (Optica Publishing Group, 2014)
Random Laser generation can give valuable information on the structure of diffuse materials. The aerogel matrix has knowingly a fractal organization. Here, random laser generation from an aerogel matrix doped with rhodamine 6G was established.